Role of Subconjunctival Bevacizumab in Treatment of Pterygium - Sayed Iqbal Assif, Rashid Omar, Sarosh Rimsha, Raja Waseem, Rashid Arshad, Banday Shahid Shahzada (Pakistan Journal of Ophthalmology, 2018)
Purpose: To assess the efficacy and role of sub-conjunctival Bevacizumab in treatment of primary and recurrent pterygium. Material and Methods: This off-label, single-dose, interventional case series was conducted at Government Medical College Hospital in Srinagar from January 2011 to March 2011 in patients with primary pterygium. Twenty eyes of 20 patients with primary pterygium were selected and a single dose of subconjunctival injection of Bevacizumab (0.05 ml, 1.25mg) was given. Pterygium vascularity and thickness was graded. The size of the pterygium (measured by surface area in cm2) was recorded from baseline to 6 weeks, after injection. Treatment-related complications and adverse events were reported. The main outcome measurements were the change in size, vascularity and thickness. Results: There were 15 males (75%) and 5 females (25%) of 20 patients with a mean age of 45.5years (SD 11.68 years). There was a significant difference in the mean surface area of pterygium at different intervals (P < 0.05) and the size of pterygium were reduced. On comparison of the mean pterygium size, there was no significant difference between men and women (P >0.05). Conclusion: Sub-conjunctival bevacizumab injection is useful in management of patients with primary pterygium without local or systemic adverse effects.